(untitled) (Nigerian Journal of Technology, 2017)
This research paper expounds microcontroller based binaural digital hearing aids for hearing-impaired people by making use of ATmega328 microcontroller and other circuitries to process the audio signal input by either increasing or reducing the gain level of input audio signal, filter background noise, frequencies compression, save battery power and minimize circuit by making use of the internal ADC of the microcontroller and two PMW pins of the microcontroller as DAC. Hearing impairment among the youths and adults nowadays are in the increase, due wrong use of phones of which every minute of the day someone’s earphone is on listening to one type of music or the other. In other to solve the problem created so to say this research work was conceived and given birth to. The different stages of digital hearing aid are designed and then simulated first in Proteus software which then was implemented using PCB-board. The main components of this system were the audio input unit which consists of the microphone and its pre-amplifier, the microcontroller (ATmega328) which consists of the ADC, the DAC and the audio signal processing, the filter stage and control codes (frequencies compression codes, power saver codes, acoustic feedback control codes, signal level control and adaptive adjustment codes etc.), the power amplifier and volume control unit and then the earphones (output). The control codes were written in C language while Ardinuo Uno compiler was used to write the codes into ATmega328. The prototype has an overall system gain of 27dB and the power output of 32.5mW. The prototype was tested with a patient that has a hearing impairment and the patient was satisfactory with the device. http://dx.doi.org/10.4314/njt.v36i3.34